Maladera rugosa (Blanchard, 1850) new combination—a valid species and senior synonym of Maladera graeca Petrovitz, 1969 (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) - Ahrens, Dirk; Pacheco, Thaynara L. (Zootaxa, 2020)
Maladera Mulsant & Rey, 1871 occurs in the Palaearctic, Oriental and Afrotropical regions and comprises already more than 300 species only in the Palaearctic alone (Ahrens & Bezděk 2016). In the past years the species of eastern West Palaearctic including Iran has been exhaustively explored and many new taxa were added (e.g. Ahrens 2000a,b, 2006; Ahrens et al. 2016; Fabrizi et al. 2018; Keith & Ahrens 2002; Keith 2005, 2010; Sabatinelli 1977; Sehnal 2008; Sehnal & Simandl 2008; Montreuil & Keith 2009; Montreuil 2016). While new collecting activities focused principally on the Iranian fauna (Nikodyìm & Král 1998; Keith & Ahrens 2002; Keith 2005, 2010; Montreuil & Keith 2009; Montreuil 2016), from where practically no records before the 1980s were available, no recent data were published on Maladera species of Europe and Minor Asia since the last taxonomic revision of the West Palaearctic species of the genus (Petrovitz 1969).